Is TNF alpha a mediator in the co-existence of malaria and type 2 diabetes in a malaria endemic population? - Ademola, Subulade A.; Bamikole, Oluwayemi J.; Amodu, Olukemi K. (Frontiers in Immunology, 2023)
Malaria remains a disease of public health importance globally, especially in sub-Saharan Africa. Malaria deaths reduced globally steadily between 2000-2019, however there was a 10% increase in 2020 due to disruptions in medical service during the COVID-19 pandemic. Globally, about 96% of malaria deaths occurred in 29 countries; out of which, four countries (Nigeria, the Democratic Republic of the Congo, the Niger, and the United Republic of Tanzania) accounted for just over half of the malaria deaths. Nigeria leads the four countries with the highest malaria deaths (accounting for 31% globally). Parallelly, sub-Saharan Africa is faced with a rise in the incidence of Type 2 diabetes (T2D). Until recently, T2D was a disease of adulthood and old age. However, this is changing as T2D in children and adolescents is becoming an increasingly important public health problem. Nigeria has been reported to have the highest burden of diabetes in Africa with a prevalence of 5.77% in the country. Several studies conducted in the last decade investigating the interaction between malaria and T2D in developing countries have led to the emergence of the intra-uterine hypothesis. The hypothesis has arisen as a possible explanation for the rise of T2D in malaria endemic areas; malaria in pregnancy could lead to intra-uterine stress which could contribute to low birth weight and may be a potential cause of T2D later in life. Hence, previous, and continuous exposure to malaria infection leads to a higher risk of T2D. Current and emerging evidence suggests that an inflammation-mediated link exists between malaria and eventual T2D emergence. The inflammatory process thus, is an important link for the co-existence of malaria and T2D because these two diseases are inflammatory-related. A key feature of T2D is systemic inflammation, characterized by the upregulation of inflammatory cytokines such as tumour necrosis factor alpha (TNF-α) which leads to impaired insulin signaling. Malaria infection is an inflammatory disease in which TNF-α also plays a major role. TNF-α plays an important role in the pathogenesis and development of malaria and T2D. We therefore hypothesize that TNF-α is a vital link in the increasing co-existence of T2D.